2022
DOI: 10.1038/s41419-022-05060-9
|View full text |Cite
|
Sign up to set email alerts
|

A dopamine-methacrylated hyaluronic acid hydrogel as an effective carrier for stem cells in skin regeneration therapy

Abstract: Adipose-derived stem cells (ADSCs) show potential in skin regeneration research. A previous study reported the failure of full-thickness skin self-repair in an injury area exceeding 4 cm in diameter. Stem cell therapies have shown promise in accelerating skin regeneration; however, the low survival rate of transplanted cells due to the lack of protection during and after transplantation leads to low efficacy. Hence, effective biomaterials for the delivery and retention of ADSCs are urgently needed for skin reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Most in vivo studies, including bilayer dressings, are evaluated in small mammals, especially rats, mice, rabbits, or guinea pigs due to their cost and easy-to-handle processes [62][63][64]. Recently, in vivo studies were performed with dopamine-modified materials that have also been shown to heal wounds in these small mammals, including rats and mice [65][66][67][68]. To our knowledge, only a few studies have used the pig model, as a result of expensive studies and difficulties due to its size [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…Most in vivo studies, including bilayer dressings, are evaluated in small mammals, especially rats, mice, rabbits, or guinea pigs due to their cost and easy-to-handle processes [62][63][64]. Recently, in vivo studies were performed with dopamine-modified materials that have also been shown to heal wounds in these small mammals, including rats and mice [65][66][67][68]. To our knowledge, only a few studies have used the pig model, as a result of expensive studies and difficulties due to its size [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…74 Hyaluronic acid can bind to stem cells and can be useful for accelerating wound healing. Gong et al 75 developed a novel hyaluronic acid-based scaffold for skin regeneration therapy. The hyaluronic acid was covalently cross-linked with methacrylate anhydride, and then the product was covalently cross-linked with dopamine to design dopamine-methacrylate hyaluronic acid (DA-MeHA).…”
Section: Materials For Skin Scaffoldsmentioning
confidence: 99%
“…Bioadhesiveness in HA hydrogels, which facilities the reconnection of skin tissue in a fast and efficient way, has been acquired by taking inspiration from mussels and, thus, introducing protein–catechol groups, either as PDA NPs 73 or by chemical modification of the HA backbone. 74,75 In fact, the tendency now is to prepare smart bioadhesive materials, in that they incorporate a biosensing function (in some cases wireless) that allows for real-time and precise evaluation of the healing stage. 76 Within this context, by using Li + and Na + as conductive ions, Lv et al designed mussel-inspired conductive HA hydrogels by employing borax as a dynamic cross-linking agent.…”
Section: Achieving Multifunctional Performancementioning
confidence: 99%